P086 Rheum to improve: a study on rheumatology knowledge amongst medical students. (26th April 2021) - Ng, Wan Lin; Devlin, Joe; Fraser, Alexander
Abstract: Background/Aims Medical students are tomorrow's doctors and rheumatology seems to be losing its status in school curricula despite its rise in importance. The aim of this study is to determine the knowledge of common rheumatic diseases amongst Year 3 graduate-entry medical students (GEMS) before and after a session of rheumatology tutorial. Methods 19 GEMS who were soon to sit for Year 3 final examination were asked to complete questionnaires pre and post rheumatology tutorial regarding their knowledge and confidence in examining/managing rheumatic diseases namely rheumatoid arthritis(RA), psoriatic arthritis(PsA), osteoarthritis(OA), gout, systemic lupus erythematosus (SLE), scleroderma and ankylosing spondylitis (AS). Knowledge and confidence were measured using a 5-point Likert scale. Results Students were aged 21-30 years. None had previous rotation in rheumatology but 2 (10.5%) had attended a rheumatology clinic before. All were not completely confident in examining the seven rheumatic conditions. >50% were somewhat or fairly confident in examining patients with RA, PsA, OA and gout. The majority found themselves either slightly or not confident in examining SLE, scleroderma and AS patients. Only one stated to have excellent knowledge on the treatment/management of one rheumatic condition, which was gout. 80% or more have above average knowledge on treatment/management of RA, OA and gout. 47.4% rated their knowledge to be poor in the treatment/management of PsA and SLE. Knowledge on treatment/management of scleroderma and AS was below average in > 84%. Following a rheumatology tutorial, everyone had confidence in examining all seven rheumatic diseases. 78.9% and above were either fairly or completely confident in examining patients with RA, PsA, OA, gout, scleroderma and AS versus 52.6% for SLE. All were above average in treating/managing RA, PsA, OA and gout. 78.9% or more have above average knowledge in treatment/management conditions like SLE, scleroderma and AS. Everyone who attended the tutorial felt that it contributed positively in their preparation towards examination and would like to have similar tutorials in future. Conclusion Knowledge in examining, treating and managing common rheumatic diseases is very poor amongst medical students. Rheumatology tutorials are beneficial to increase their knowledge and confidence. Attendance in rheumatology clinics should also be encouraged. Disclosure W. Ng: None. J. Devlin: None. A. Fraser: None.